Process intensification for scalable synthesis of ytterbium and erbium co-doped sodium yttrium fluoride upconversion nanodispersions - Pu, Y.; Leng, J.; Wang, D.; Wang, J.; Foster, Neil; Chen, J. (Elsevier, 2018)
© 2018 Elsevier B.V. Rare-earth doped NaYF4upconversion nanomaterials have found many applications from biosensing through photoelectric conversion to luminescent anti-counterfeiting. However, the scalable synthesis methods of ultrasmall NaYF4nanoparticles are still challenging. Herein, We demonstrated that the intensified mixing of the precursor by a high-gravity rotating packed bed (RPB) reactor before the hydrothermal synthesis process enabled the preparation of ultrasmall NaYF4:Yb3+/Er3+upconversion nanoparticles, with much smaller size, more uniform distributions and higher Er3+-doping level than those obtained in the stirred tank reactor (STR) route. In stark contrast to conventional synthetic techniques that require stringent control over several experimental variables for controlling morphologies and sizes, the process intensification approach presented here requires modification of only a single variable while enabling tremendous improvements to control the formation of NaYF4based UCNPs with small feature size. The UCNPs dispersed well in various organic solvents (e.g. ethanol, acetone, toluene, cyclohexane, etc.), forming transparent nanodispersions with upconversion luminescence under 980 nm NIR light irradiation. The preliminary applications of NaYF4:Yb3+/Er3+nanodispersions for upconversion luminescent transparent hybrid films and anti-counterfeiting were also demonstrated.